Relationship between Emergency Level (Triage) and Anxiety Level of the Patient's Family - Lasman, Lasman; Islamy, Aesthetica; Farida, Farida; Nurhidayati, Nurhidayati; Rohmawati, Indah; Osella, Dea (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
Anxiety is an emotional response to an assessment that describes a state of worry, anxiety, fear, and unrest accompanied by various physical complaints. During the treatment process, anxiety is not only felt by a patient but can also be experienced by the patient's family. The patient's family is one of the full decision-holders when the patient is in an emergency or critical condition and must be given immediate treatment. The research objective was to determine the relationship between the level of emergency (triage) and the anxiety level of the patient's family. The research design used was a cross-sectional analysis, the study was carried out on 30 May-13 June 2018 at the Emergency Room of RSUD Dr. Iskak Tulungagung. The sample in this study was the patient's family using a consecutive sampling technique, a sample of 30 respondents was obtained. Data was collected using the HARS questionnaire. Data were processed by editing, coding, scoring, tabulating, and analyzing with Spearman's rho statistical test. The results of the Spearman's rho statistical test, obtained a value of p = 0.000 to test the relationship between the level of emergency (triage) and the anxiety level of the patient's family. With a significant level value of ï¡ = 0.05, which means there is a relationship between the level of emergency (triage) and the anxiety level of the patient's family. The conclusion from this study is that the higher the level of emergency (triage) of the patient, the more anxiety of the patient's family will affect. Recommendations for hospitals, especially in the Emergency Room, are expected to further improve communication between health workers and patient families. To reduce the possibility of anxiety by the family.Relationship between Emergency Level (Triage) and Anxiety Level of the Patient's Family.